Identify predictive factors for the emergence of self-reported oropharyngeal dysphagia in older men and women populations: a retrospective cohort analysis - Liu, Shuang; Fan, Ling-Jie; Tian, Hao; Wei, Sha-Sha; Zhang, Si-Jie; He, Mei; Wei, Ji-Hong (Frontiers in Neurology, 2025)
Background and objectivesOropharyngeal dysphagia (OD) is an emergent health concern in older adults, with incidence rates escalating due to age-related and various neurological and physical conditions. This study identifies risk and protective factors for new-onset OD, with an emphasis on gender differences.MethodsUtilizing data from the National Health and Aging Trends Study (NHATS), this study analyzed 6,360 participants (58.1% women) across 2011–2014 and 2015–2018 periods. Employing a random forest feature selection, specifically recursive feature elimination and mean decrease impurity algorithm, we assessed 128 variables to identify critical factors including demographics, health, physical and neurological functionality, and environmental conditions. The study further applied logistic regression and explored factor interactions using restricted cubic splines, streamlining the analysis to focus on key determinants of oropharyngeal dysphagia.ResultsInitial findings show a decrease in new-onset OD from 15.62% in 2011 to 14.49% in 2015, with women more frequently affected. The analysis elucidates a constellation of highly predictive factors for OD, encompassing extremes of body mass index (BMI), socioeconomic challenges (as indicated by low income), diminished physical conditioning, and adverse emotional states. Notably, gender-specific disparities emerged, highlighting the critical role of cognitive function and mood in men, whereas in women, the overarching influence of general health status and comorbidities was more pronounced.ConclusionThis condensed examination highlights the complex, multifactorial nature of OD in older adults, influenced by sociodemographic, physical, and psychological factors, and underscores the need for gender-specific approaches in predicting, preventing, and managing OD.